(untitled) (Research, Society and Development, 2020)
The purpose of this research was to look for validity evidences for the Portuguese version of Maslach Burnout Inventory-Educators Survey (MBI-ES) based on its relationship with psychological (sense of coherence, resilience, depression and anxiety) and sociodemographic variables (sex, level of education taught, civil status, to have children or not, age, education, years of experience and number of children) in Mozambican and Brazilian teachers. A sample of 512 elementary school teachers was investigated, 278 Mozambican and 234 Brazilian. Correlation analysis showed that burnout factors were negative correlated with sense of coherence and resilience, and positive correlated with depression and anxiety. Effects of sociodemographic variables were found within both nationalities. These results are compatible with previous ones found in the international literature, and may be considered as evidence of MBI validity.